Rajasthan flood as viewed by SAMIR onboard Bhaskara (MAUSAM, 1980)
Data from Satellite Microwave Radiometer (SAMIR) onboard India's second satellite Bhaskara have been analysed for orbit Nos. 473 (8 July 1979), 607 (17 July 1979) and 890 (5 August 1979). These data correspond to the pre and post flood period over Luni river basin in Rajasthan. The limited observations show the separability of dry land from flooded area using SAMIR.